Genetically Engineered Bacillus thuringiensis Var-israelensis (bti) for the Biological Control of Mosquito-A Review - Nandadasa, H.G. (My University, 1991)
The number of pathogenic microorganisms that are capable of killing insect pests is extremely large. Some bacteria are more attractive to researchers developing microbial biological control agents because their genomes are simple enabling easier study and manipulation. Several bacterial species are already used on a large scale as control agents against some insects. Commercial preparation of these bacteria in theform of insecticidal powders are available for use in the field. Although these preparations are somewhat more expensive and also less e/jicient than chemical insecticides, for several reasons including recent awareness of environmental safety, development of biological control agents has recieved increased attention of biologists. Several varieties of Bacillus thuringiensis have been well studied for their to:xic effects on insects. These bacteria produce proteinaceous parasporal crystals during their sporulation. When these crystals are ingested by insect larvae protein protoxins are solubilised in the alkaline environment of the insect midgut releasing polypeptides toxic to the epithelial cells resulting in quick death of the larvae. Toxicity of Bacillus thuringiensis var. israelensis is specific to mosquito and blackfly larvae. However, large scale use of this bacterium for the control of mosquitoes is limited by its low persistenee in the field after application. Four genes coding for 4 different toxic polypeptides have been isolated from this bacterium and all these have been cloned in E. coli and studied. Research is being done to study the posible manipulation of these genes in order to obtain potentially much more efficient bacterial strains for the control of insects.
Keywords: genetically engineered; bti; mosquito control